عوامل صعوبات التعليم في مهارة الكلام لطلبة الصفّ الثامن بالمدرسة "اقرأ" المتوسطة الإسلامية المتكاملة بنجكولو - Nur Hariyanto; Falahun Ni'am; M Zikri (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
This study aimed to determine the factors of teaching difficulties in teaching speaking skills and the efforts made by the teacher to overcome these problems among eighth grade students. Difficulty factors in teaching speaking skills to eighth grade students at Integrated Islamic Middle School, Bengkulu, 2020. Bengkulu: Department of Arabic Language Teaching, College of Education and Teacher Training, Bengkulu Islamic University, 2020. The background of this research is that speaking is still the ability of eighth grade students in the stage high school. The integrated Islamic 'Iqra' Bengkulu is incomplete because only a few of them speak Arabic. When teachers ask students to speak Arabic, students will not be able to convey ideas properly, and they will be fearful, shy, and bossy. Improve students' courage and speaking skills in the classroom. Therefore, teachers should be able to encourage their students to speak up even if it is wrong. This study aimed to determine the factors of teaching difficulties in teaching speaking skills and the efforts made by the teacher to overcome these problems among eighth grade students. This research is a field research, a field database and supporting documents in this research, full of data from an interview with an Arabic language teacher and eighth grade students, and the results of observation before research. The method of data collection used in this research. The research is the method of observation, the method of the interview, and the method of documentation. The results of the research indicate that the presence of learning difficulties factors in speech skill means heterogeneous backgrounds of students, students' lack of interest in learning their pronunciation skills, and the absence of any disciplinary rules for students who use the Arabic language. Language The amount of material must be mastered and not all other pupils who choose the reasons for the class language. Often the teacher's efforts in teaching speech skills are teachers who do Arabic speaking exercises and provide good examples to the pupils as well as collaborate with parents so that the pupils are attentive.